Study on technology characteristics materials based on polysulfone - A. B. Baranov; O. E. Peksimov; T. N. Prudskova; T. A. Andreeva; I. D. Simonov-Emelyanov; N. L. Shembel (Тонкие химические технологии)
The research covers rheological characteristics of melts of polysulfones of domestic brand PSF-190 and foreign brand Udel P-1700 at temperatures ranging from 290 to 360°C. The values of activation energy of viscous flow of polysulfone melts at different temperatures are presented. The flow behavior indexes of melts of polysulfones PSF-190 and Udel P-1700 were determined. For the first time thermal stability curves over a wide temperature range were obtained, and formulas for describing them were presented. Temperature modes for processing the studied polysulfones were suggested. The dependency of density and volume in the temperature range from 23 to 320°C were obtained by the dilatometric method. Besides, constants and coefficients of the state equation of linear thermal expansion were calculated.